2001
DOI: 10.1021/ja010277e
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Selectivities in C−H Activations of Toluene andp-Xylene at Cationic Platinum(II) Diimine Complexes. New Mechanistic Insight into Product-Determining Factors

Abstract: The C-H activation of toluene and p-xylene at cationic Pt(II) diimine complexes (N-N)Pt(CH(3))(H(2)O)(+)BF(4)(-) (N-N = Ar-N=CMe-CMe=N-Ar; 1(BF(4)(-)), N(f)-N(f), Ar = 3,5-(CF(3))(2)C(6)H(3)); 2(BF(4)(-)), N'-N', Ar = 2,6-(CH(3))(2)C(6)H(3)) has been investigated. The reactions were performed at ambient temperature in 2,2,2-trifluoroethanol (TFE), and after complete conversion of the starting material to mixtures of Pt-aryl/Pt-benzyl complexes and methane, acetonitrile was added to trap the products as more st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 51 publications
5
96
1
Order By: Relevance
“…The inhibition of isotopic scrambling by the addition of a Lewis base is most readily explained by an associative mechanism for exchange of ethylbenzene with THF and mirrors the observations of isotope exchange from protonation of (diimine)Pt(Me) 2 using DOTf, as well as positional o/m/p isomerization of Pt tolyl and xylyl complexes where NCMe was used as the Lewis base in both cases. 39,40 To confirm the interpretation of the results of isotopic labeling, [( , has a high calculated barrier (ΔG q = 27.5 kcal/mol), consistent with the absence of extensive H/D scrambling into the ethyl fragment. The free energy for dissociation of ethylbenzene from A 0 is calculated to be 12.5 kcal/mol (Scheme 19; these calculations are gas phase and thus the free energy of ethylbenzene dissociation is different from that in Scheme 8), while arene CÀH activation barriers are calculated to be 16.2 kcal/mol (para CÀH activation), 16.7 kcal/ mol (meta CÀH activation) and 18.7 (ortho CÀH activation).…”
mentioning
confidence: 76%
“…The inhibition of isotopic scrambling by the addition of a Lewis base is most readily explained by an associative mechanism for exchange of ethylbenzene with THF and mirrors the observations of isotope exchange from protonation of (diimine)Pt(Me) 2 using DOTf, as well as positional o/m/p isomerization of Pt tolyl and xylyl complexes where NCMe was used as the Lewis base in both cases. 39,40 To confirm the interpretation of the results of isotopic labeling, [( , has a high calculated barrier (ΔG q = 27.5 kcal/mol), consistent with the absence of extensive H/D scrambling into the ethyl fragment. The free energy for dissociation of ethylbenzene from A 0 is calculated to be 12.5 kcal/mol (Scheme 19; these calculations are gas phase and thus the free energy of ethylbenzene dissociation is different from that in Scheme 8), while arene CÀH activation barriers are calculated to be 16.2 kcal/mol (para CÀH activation), 16.7 kcal/ mol (meta CÀH activation) and 18.7 (ortho CÀH activation).…”
mentioning
confidence: 76%
“…One important finding has been that low-temperature protonation of (diimine)Pt(II) dialkyl and Pt(II) diaryl complexes lead to observable, but thermally sensitive, Pt(IV) hydridoalkyl and hydridoaryl complexes that eliminate the respective hydrocarbons upon heating. 60,[76][77][78][79][80][81] Scheme 9 summarizes the mechanistic picture that has emerged for these reactions at (diimine)Pt(II) systems 60,63,74,[82][83][84][85] and at related Pt species with bidentate ligands. Substitution of π-benzene for an aqua (or TFE) ligand occurs as a solvent assisted process for which there is controversy over an associative mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…These differences reflect the increased steric demands of the 2,6-dimethyl-substituted systems and appear to be a common feature for N,NЈ-diaryl-substituted (N-N)PtX 2 complexes where similar trends in dihedral angles have been reported. [15,36,44,45,54,60,[62][63][64][65][66][67] This empha-sizes the steric hindrance imposed by the 2,6-dimethyl-substituted N-aryl groups: The perpendicular orientation of these N-aryl groups with respect to the coordination plane causes the methyl groups to sterically block the access to Pt from above and below the coordination plane. This has a pronounced effect on the qualitative protonation rates and on the stabilities of the Pt II π-benzene complexes, as discussed earlier.…”
Section: Synthesis and Characterization Of Metal Complexesmentioning
confidence: 99%
“…On the other hand, the η 2 -benzene complexes will be stabilized by the 2,6-dimethyl groups because the displacement of benzene (and other hydrocarbons) from these and related diimine-Pt complexes has been demonstrated to be associative reactions. [32,59,60] Scheme 4. It has been demonstrated that the kinetically preferred site of protonation is the Pt center for (Ar-DAB)PtMe 2 complexes. [17,18] We have recently presented experimental evidence that this is also the case for (Ar-DAB)PtPh 2 analogues, [32] a scenario that had already been predicted by DFT calculations.…”
Section: Synthesis and Characterization Of Metal Complexesmentioning
confidence: 99%